The Alpha Isoform of Heat Shock Protein 90 and the Co-chaperones p23 and Cdc37 Promote Opioid Anti-nociception in the Brain - Lei, Wei; Duron, David I.; Stine, Carrie; Mishra, Sanket; Blagg, Brian S. J.; Streicher, John M. (Frontiers in Molecular Neuroscience, 2019)
Opioid activation of the mu opioid receptor (MOR) promotes signaling cascades that evoke both analgesic responses to pain and side effects like addiction and dependence. Manipulation of these cascades, such as by biased agonism, has great promise to improve opioid therapy. However, the signaling cascades of the MOR are in general poorly understood, providing few targets for drug development. In our earlier work, we identified Heat shock protein 90 (Hsp90) as a novel and crucial regulator of opioid anti-nociception in the brain by promoting ERK MAPK activation. In this study, we sought to identify the molecular isoforms and co-chaperones by which Hsp90 carried out this role, which could provide specific targets for future clinical intervention. We used novel selective small molecule inhibitors as well as CRISPR/Cas9 gene editing constructs delivered by the intracerebroventricular (icv) route to the brains of adult CD-1 mice to target Hsp90 isoforms (Hsp90α/β, Grp94) and co-chaperones (p23, Cdc37, Aha1). We found that inhibition of the isoform Hsp90α fully blocked morphine anti-nociception in a model of post-surgical paw incision pain, while blocking ERK and JNK MAPK activation, suggesting Hsp90α as the main regulator of opioid response in the brain. We further found that inhibition of the co-chaperones p23 and Cdc37 blocked morphine anti-nociception, suggesting that these co-chaperones assist Hsp90α in promoting opioid anti-nociception. Lastly, we used cycloheximide treatment in the brain to demonstrate that rapid protein translation within 30 min of opioid treatment is required for Hsp90 regulation of opioid response. Together these studies provide insight into the molecular mechanisms by which Hsp90 promotes opioid anti-nociception. These findings thus both improve our basic science knowledge of MOR signal transduction and could provide future targets for clinical intervention to improve opioid therapy.